THE USING OF TECHNOLOGY ACCEPTANCE MODEL IN UNDERSTANDING THE APPLICATION PROCESS OF INDONESIAN ACCOUNTING STANDARDS FOR NON-PUBLICLY-ACCOUNTABLE ENTITIES IN SMEs IN PONTIANAK - Astarani, Juanda; Kurniasih, Mardiana (JAAKFE UNTAN (Jurnal Audit dan Akuntansi Fakultas Ekonomi Universitas Tanjungpura), 2020)
This study aims to analyze the application of Indonesian Accounting Standards for Non-Publicly-Accountable Entities in SMEs in Pontianak City using Technology Acceptance Model (TAM). This study was conducted in the Pontianak City area using primer data in a form of questionnaire. The total sample in this research was 50 SMEs that were randomly selected. Statistic test used in the data management was Partial Least Square (smartPLS 3.0). The finding of this research shows that the perceived ease of use significantly affects the perceived usefulness and attitude toward using the Indonesian Accounting Standards for Non-Publicly-Accountable Entities, while the perceived usefulness significantly affects the attitude towards using IndonesianAccounting Standards for Non-Publicly-Accountable Entities. Moreover, the attitude toward using the Indonesian Accounting Standards for Non-Publicly-Accountable Entities significantly affects the behavioural intention to use Indonesian Accounting Standards for Non-Publicly-Accountable Entities.Keywords : Technology Acceptance Model (TAM), Indonesian Accounting Standards for Non-Publicly-Accountable Entities, SMEs